Dielectric Frequency Response Analysis of 230 kV Service Aged OIP and RIP Bushings: Case Studies - Pattanadech, Norasage; Jeenmuang, Siwakorn; Ostria, Elmer; Suksagoolpanya, Suthat (My University, 2025)
Transformer bushings are critical components that enable current to pass through the transformer enclosure while providing insulation between the high-voltage conductor and the grounded housing. A failure in the bushing could potentially result in transformer failure. This paper presents case studies on the evaluation of 230 kV Oil-Impregnated Paper (OIP) and 230 kV Resin-Impregnated Paper (RIP) bushings using Dielectric Frequency Response (DFR) analysis. The bushings investigated in this study were service-aged units removed from the field. For the 230 kV OIP bushing, the paper insulation was peeled off starting from the outermost layer. This allowed for DFR testing on individual insulation sections. The results indicated moisture absorption and provided information on the moisture distribution within the paper insulation. Furthermore, a 230 kV RIP bushing suspected of having poor contact between the outermost foil layer and the test tap connection was also investigated. The DFR results from this case revealed the observable impact of such connection issues on the DFR test. In summary, DFR analysis has proved that it is a very useful technique for testing and diagnosing various common bushing degradation mechanisms that can lead to severe failure of the bushings and the transformers.
Keywords: dielectric frequency response; Oil impregnated paper bushing; Resin impregnated paper bushing